Estimated Prevalence and Incidence of Disease-Associated Human Papillomavirus Types Among 15- to 59-Year-Olds in the United States. Issue 4 (26th April 2021) - Lewis, Rayleen M.; Laprise, Jean-François; Gargano, Julia W.; Unger, Elizabeth R.; Querec, Troy D.; Chesson, Harrell W.; Brisson, Marc; Markowitz, Lauri E.
Abstract : In 2018, in the United States, 42.5 million persons were infected with 1 or more human papillomavirus types that can cause human papillomavirus–associated precancers/cancers or anogenital warts; 13 million persons acquired a new infection. Supplemental digital content is available in the text. Abstract : Introduction: Human papillomavirus (HPV) can cause anogenital warts and several types of cancer, including cervical cancers and precancers. We estimated the prevalence, incidence, and number of persons with prevalent and incident HPV infections in the United States in 2018. Methods: Prevalence and incidence were estimated for infections with any HPV (any of 37 types detected using Linear Array) and disease-associated HPV, 2 types that cause anogenital warts plus 14 types detected by tests used for cervical cancer screening (HPV 6/11/16/18/31/33/35/39/45/51/52/56/58/59/66/68). We used the 2013–2016 National Health and Nutrition Examination Survey to estimate prevalence among 15- to 59-year-olds, overall and by sex. Incidences in 2018 were estimated per 10, 000 persons using an individual-based transmission-dynamic type-specific model calibrated to US data. We estimated number of infected persons by applying prevalences and incidences to 2018 US population estimates. Results: Prevalence of infection with any HPV was 40.0% overall, 41.8% in men, and 38.4% in women; prevalence of infection with disease-associated HPV was 24.2% in men and 19.9% in women. An estimated 23.4 and 19.2 million men and women had a disease-associated HPV type infection in 2018. Incidences of any and disease-associated HPV infection were 1222 and 672 per 10, 000 persons; incidence of disease-associated HPV infection was 708 per 10, 000 men and 636 per 10, 000 women. An estimated 6.9 and 6.1 million men and women had an incident infection with a disease-associated HPV type in 2018. Conclusions: We document a high HPV burden of infection in the United States in 2018, with 42 million persons infected with disease-associated HPV and 13 million persons acquiring a new infection. Although most infections clear, some disease-associated HPV type infections progress to disease. The HPV burden highlights the need for continued monitoring of HPV-associated cancers, cervical cancer screening, and HPV vaccination to track and prevent disease.